Analysis of Medical Records Unit Employee Workload During the COVID-19 Pandemic at Mitra Masyarakat Hospital, Mimika, Indonesia - Raru, Amida Morina; Siswati; Deasy Rosmala Dewi; Nanda Aula Rumana (Open Access Indonesian Journal of Medical Reviews, 2023)
The workload of medical record unit staff at a hospital can vary depending on the size and type of hospital, the number of patients, and the internal policies implemented. Medical record unit employees are responsible for collecting, managing, and storing patient medical records. During the COVID-19 pandemic, the workload of employees in the medical records unit greatly increased because there was a surge in patients due to the pandemic. An increase in the number of patients occurred in all hospitals in Indonesia, including Mitra Masyarakat Hospital, Mimika. This study aimed to describe the workload profile of employees in the medical records unit at Mitra Masyarakat Hospital during the COVID-19 pandemic. This research is descriptive observational research. The location of this research is Mitra Masyarakat Hospital, Mimika, Indonesia. The research was conducted from March to August 2021. Data sources were obtained from interviewing informants, observing and measuring workload in the medical record unit before and during the pandemic. The variables measured in this study were available working time, workload standards, supporting task standards, and supporting task factors, as well as the need for human resources in the Mitra Masyarakat Hospital work unit. The results of the study show that the available working time for medical record unit personnel for each section is 1300 hours/year or 78,000 minutes/year. The need for health human resources for the medical record unit is as many as 20 people. There are 9 medical record officers currently owned by RSMM. Thus it can be concluded the number of employees is less when compared to the workload in the medical record unit at Mitra Masyarakat Hospital.